Віртуальна власність з позиції цифрової інтелектуальної економіки: теоретичні засади цифрового права - Бутнік-Сіверський, Олександр Борисович (My University, 2023)
У статті розглядається формування людино-цифрового середовища з позиції реального та віртуального, де домінують права людини на об’єкти інтелектуальної власності при використанні цифрових інструментів. Узагальнено наукові погляди на речове право як особливий вид права власності, об’єктом якого є безтілесні речі або безтілесне майно. Досліджено віртуалізацію власності, де формуються людино-цифрові системи з використанням новітніх цифрових технологій з додержанням цифрового права. Визначено ознаки віртуального права інтелектуальної власності стосовно реального права інтелектуальної власності. The article examines the formation of a human-digital environment as a society using digital technologies. It is studied from the standpoint of a real and virtual or material and relatively abstract environment where the rights to intellectual property objects dominate as a digital right of a person when using digital tools that enable the use of various digital technologies, as well as fundamental digital rights that require a new understanding. It is noted that the right of virtual property should be distinguished from the right of intellectual property and defined as a specific type of property right. The virtualization of intellectual property is considered as a process of transition from digital intellectual property to digital virtual intellectual property with the corresponding signs of the development or creation of new objects that have an economic value equivalent to material things. In the conditions of digital individualization, the main feature of property rights is the domination of a person over a virtual thing. Virtual space allows the owner of virtual objects to own, use and dispose of them. On the basis of the virtualization of property in the system of using technological platforms, a human-digital system is formed using the latest digital technologies and digital communication with the observance of digital law. A more complex phenomenon is considered in which virtual owner(s) or implicit owner(s) appear, relying on artificial intelligence. In this regard, the rights are dissolved in a system of transformed computer programs and digital technologies which is gaining pace of development of the digital human rights to digital objects or instruments of virtual property. They are replaced by a virtual or conditional author, a digital administrator as a digital person or a subject of digital legal relations where the value of the real right is lost as the domination of a person over a virtual thing, and only commercial economic dominates an interest that may take the form of a monopoly in the market of digital services. Virtual property is becoming the main legal construct in the sys- tem of the digital economy of intellectual property, where there are distinctive features of virtual intellectual property rights in relation to real intellectual property rights.
Keywords: людино-цифрове середовище; цифрові права людини; віртуальна власність; речове право; цифрова інтелектуальна власність; цифрові правовідносини; human-digital environment; digital human rights; virtual property; property law; digital intellectual property; digital legal relations